The Congress of the United States - Kronenwetter, Michael (Springfield, NJ : Enslow Publishers, 1996)
Discusses the history, purpose, and functioning of the Congress of the United States and the issues facing the legislative branch of government at the end of the twentieth century.
Includes bibliographical references (p. 99-102) and index.
Keywords: United States. -- Congress -- Juvenile literature; United States. -- Congress; United States -- Politics and government -- Juvenile literature; United States -- Politics and government